1999
DOI: 10.1258/0956462991914302
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with human immunodeficiency virus infection: impact of social support, coping style and hopelessness

Abstract: We aimed to determine whether the quality of life (QOL) in the patients infected with human immunodeficiency virus (HIV) infection was influenced by satisfaction with social support, coping style and hopelessness. One hundred and thirty-eight HIV-infected patients were prospectively studied in this multicentre, longitudinal study. The QOL was assessed by Medical Outcome Study Health Survey SF-36, social support by Sarason Social Support Questionnaire, hopelessness by Beck Hopelessness Scale, and coping by Bill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 19 publications
11
68
1
1
Order By: Relevance
“…Our findings are in line with these associations, which have been previously recognised (e.g., da Silva et al, 2013;Degroote et al, 2013;Hays et al, 2000;Liu et al, 2006;Rueda et al, 2011). Because higher education and employment have been considered a proxy of a higher socioeconomic status in general, these findings are comprehensible and support the notion that socioeconomic circumstances are an important part of one's life and QoL and may provide more than simple financial benefits for PLWHA (Swindells et al, 1999). It is also likely that higher education may denote an improved ability to comprehend the treatment recommendations and, accordingly, to a better engagement in medical care, which therefore may reflect better QoL.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in line with these associations, which have been previously recognised (e.g., da Silva et al, 2013;Degroote et al, 2013;Hays et al, 2000;Liu et al, 2006;Rueda et al, 2011). Because higher education and employment have been considered a proxy of a higher socioeconomic status in general, these findings are comprehensible and support the notion that socioeconomic circumstances are an important part of one's life and QoL and may provide more than simple financial benefits for PLWHA (Swindells et al, 1999). It is also likely that higher education may denote an improved ability to comprehend the treatment recommendations and, accordingly, to a better engagement in medical care, which therefore may reflect better QoL.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, and yet not surprising, being unemployed (or not currently working) was associated with poorer QoL in all domains, with the exception of Spirituality. This finding is consistent with Swindells and colleagues' study [32] that suggests that employment may provide more than just financial benefits for PLWHA. Also consistent with prior work [7-9, 18, 26, 35], clinical variables (CD4?…”
Section: Discussionsupporting
confidence: 91%
“…Comparisons between educational groups showed that those with less education reported significantly poorer QoL than those with higher education [8,13,15,16,26]. Previous research that has incorporated employment status as a variable of interest verified that employed individuals generally reported enhanced QoL [26,27,31,32].…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 99%
“…It should be noted that a significant coping strategy, that is, avoidance, has not been studied here for methodological reasons. With respect to this issue, avoidance has been associated with a higher risk of depression [44], greater risk-taking behavior [45], lower adherence to antiretroviral therapy [46], poorer quality of life [47]and a slower decline in CD4 count [48]among HIV-infected patients. This area deserves further attention, both among HIV-infected as well as HCV-positive subjects.…”
Section: Discussionmentioning
confidence: 99%